JENIS-JENIS CEMPEDAK (Artocarpus champaden Lour.) DI KABUPATEN KAMPAR PROVINSI RIAU - Fitmawati Fitmawati; Via Andani; Nery Sofiyanti (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2018)
Cempedak (Artocarpus champaden Lour.) is one of the special fruits in Southeast Asia which is the prima donna of the community. In the province of Riau, cempedak found in many areas of Kampar regency. This study aims to identify the types of cempedak that exist in Kampar regency. Based on the results of the research, cempedak is categorized into four cultivars ie cempedak pulp cultivars, cempedak forest cultivars, cempedak langkat cultivars and cempedak nangkadak cultivars, from four cempedak cultivars found, Nempadak cempedak cultivars and Langkat cultivars are the most superior cempedak cultivars because they have fruits big, lots of content, thick meat and sweet taste.